2019
DOI: 10.2147/ijn.s207419
|View full text |Cite
|
Sign up to set email alerts
|

<p>A new strategy for accurate targeted diagnosis and treatment of cutaneous malignant melanoma: dual-mode phase-change lipid nanodroplets as ultrasound contrast agents</p>

Abstract: Background Currently, effective detection and treatment of cutaneous malignant melanoma (CMM) still face severe challenges. Ultrasound molecular imaging as a noninvasive and easy-to-operate method is expected to bring improvements for tumor detection. Purpose The aim of this research is to prepare novel phase-change ultrasound contrast agents, Nds-IR780, which can perform not only dual-mode molecule-targeted imaging but also targeted photothermal therapy for CMM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The experimental procedures were performed according to our previous experiments 24 , 38 . First, 2 μL of Dio (1.2 mg/mL) was added to 1 mL of SonoVue suspension to stain the microbubbles for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedures were performed according to our previous experiments 24 , 38 . First, 2 μL of Dio (1.2 mg/mL) was added to 1 mL of SonoVue suspension to stain the microbubbles for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedures were performed according to our previous experiments 24 , 38 . The biosafety of IR780-NBs-DTX was examined via a Cell Counting Kit-8 (CCK-8) assay with pancreatic cancer Mia-Paca2 cells purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated that the melanocyte-stimulating hormone conjugated AuNCs obtained a 300% imaging contrast enhance in melanoma tumor model when compared to that of the control nanocages ( Figure 2 ; Kim et al, 2010a ). Yang et al (2019) revealed a combination of dual-mode molecular-targeted ultrasound and NIR fluorescence imaging by a novel contrast agent named Nds-IR780 to precisely detect the primary lesions and sentinel lymph nodes (SLN) in cutaneous malignant melanoma. Moreover, Nds-IR780 could also serve as a theranostic probe for targeted therapy in cutaneous malignant melanoma ( Figure 1B ).…”
Section: Diagnosis and Surgical Removal Of Melanomamentioning
confidence: 99%
“…Based on the dual-mode probe with both fluorescence imaging and photothermal ability, cutaneous malignant melanoma was successfully ablated. Reproduced with permission ( Yang et al, 2019 ). Copyright 2019, Dove Medical Press Ltd.…”
Section: Diagnosis and Surgical Removal Of Melanomamentioning
confidence: 99%
“…Based on the targeted accumulation capacity of Au-PFH-NPs andC-Au-PFH-NPs in tumor cells, we explored the potential ofphase-changing nanoparticles to aid as US contrast to improve USIand treatment scratches [55][56][57]. Following the administration ofvarious medicines before LIFUS irradiation, even lower or anechoiccontrast improved US signals were observed in each group( Figure 6A).…”
Section: In Vitro Ultrasound Imagingmentioning
confidence: 99%